The pricing of audit service: Futher evidence from UK banking industry - Mei, ShengLun (2012)
1. Abstract There has been more and more literature to investigate determinants of audit fees and different authors have crossed border of countries under different audit settings to provide evidence of determinants which may influence audit fee. Analyze the determinants of audit fee is to investigate the capital structures of auditing firms, forecast the future trend of audit fees and measure quality, effectiveness, competence of auditing firms. Although there has been more and more literature to analyze audit fee determinants, until now no study has analyzed the audit fees determinants for the UK banking. This study aims to provide some creative theory and evidence regarding the audit pricing for the UK banks. And main target of this thesis is to investigate determinants that may have influence on external audit pricing in the UK. In order to investigate the influence of determinants, including client size, client complexity, client profitability, client risk, non audit fee, the effect of subsidiary of multinational corporation and the effect of big auditor, the traditional ordinary least square regression audit fee model is used. This paper seeks to investigate the audit fee by obtaining a sample of 50 biggest UK banks during the period of 2006-2010. It is should be noticed that the amount of sample is reduced from 89 to 50, this is mainly due to although the legislation requires each UK bank to disclose the detail regarding the amount of audit fee paid to auditors, some of UK banks, which did not disclose the detail of audit fee or non audit fee in the annual reports as legislation. Consistent with expectation, the results provide strong evidence to support that most of findings from previous studies are also in line with the UK banking, it illustrates that the audit fee is influenced by client size, client complexity, non audit fee, client risk, the effect of subsidiary of multinational corporation. Non-significant relationship is found between the audit fee and return on equity (ROE) and big auditor effect. This study also shows that some other important issues should be taken into consideration, like individual auditor effect, sensitivity analysis, comparison between big bank and small bank, comparison between independent and subsidiary bank, comparison between public company and private company, and comparison between investment bank, commercial bank, and holding bank.